Review of Proton Pump Inhibitor Overuse in the US Veteran Population - Metaxas, Evdokia S. (J Pharm Technol, 2015)
Objective: A growing body of evidence provides proof that proton pump inhibitors (PPIs) are overused in the general population and that such use is associated with adverse risks and unnecessary costs. Our objective was to systematically evaluate PPI overuse in the veteran population. Data Sources: A literature search using MEDLINE and CINHAL databases (1946-December 2014) was performed using the search term proton pump inhibitors coupled with each of the following key words: inappropriate use, misuse, and overuse. Searches were limited to studies and reviews in English language and human subjects. Additional references were identified from a review of literature citations. Study Selection and Data Extraction: All articles that centrally addressed the issue of PPI overuse were evaluated, following the PRISMA guidelines for systematic reviews. Data were extracted into Microsoft Excel 2013. Articles that focused on the pediatric or non-US veteran populations were excluded. Data Synthesis: Among 30 articles included, 5 evaluated PPI overuse in veterans. The reported prevalence rate of PPI overuse in veterans ranged from 33% to 67%. Several cases reported PPI-associated Clostridium difficile–associated diarrhea and pneumonia. One Veterans Affairs center reported the total cost of PPI overuse to be more than $200 000 based on over-the-counter costs and more than $1.5 million based on average wholesale price cost. Conclusions: PPI overuse is common among veterans and exposes them to adverse risks and costs the system enormous dollars. Based on the findings of this review, we provide recommendations to curb PPI overuse among veterans and in the Veterans Affairs system.